Propriedades física de molécilas orgânicas e compostos do tipo perovskita CdSiO3 e CaPbO3 - Barboza, Carlos Antônio (2009)
In the first part of this work our concern was to investigate the thermal effects in organic crystals using the theory of the polarons. To analyse such effect, we used the Fröhlich s Hamiltonian, that describes the dynamics of the polarons, using a treatment based on the quantum mechanics, to elucidate the electron-phonon interaction. Many are the forms to analyzing the polaronic phenomenon. However, the measure of the dielectric function can supply important information about the small polarons hopping process. Besides, the dielectric function measures the answer to an applied external electric field, and it is an important tool for the understanding of the many-body effects in the normal state of a polaronic system. We calculate the dielectric function and its dependence on temperature using the Hartree-Fock decoupling method. The dieletric function s dependence on the temperature is depicted by through a 3D graph. We also analyzed the so called Arrhenius resistivity, as a functionof the temperature, which is an important tool to characterize the conductivity of an organic molecule. In the second part we analyzed two perovskita type crystalline oxides, namely the cadmium silicate triclinic (CdSiO3) and the calcium plumbate orthorhombic (CaPbO3), respectively. These materials are normally denominated ABO3 and they have been especially investigated for displaying ferroelectric, piezoelectric, dielectrics, semiconductors and superconductors properties. We found our results through ab initio method within the functional density theory (DFT) in the GGA-PBE and LDA-CAPZ approximations. After the geometry optimization for the two structure using the in two approximations, we found the structure parameters and compared them with the experimental data. We still determined further the angles of connection for the two analyzed cases. Soon after the convergence of the energy, we determined their band structures, fundamental information to characterize the nature of the material, as well as their dielectrics functions, optical absorption, partial density of states and effective masses of electrons and holes